Radiation dose and quickness of needle CT-interventions using a laser navigation system (LNS) compared with conventional method. Issue 10 (October 2015) - Gruber-Rouh, T.; Schulz, B.; Eichler, K.; Naguib, Nagy N.N.; Vogl, T.J.; Zangos, S.
Highlights: LNS is a system for CT-guided interventions. LNS automatically marked skin-entry-point and direction of needle puncture. LNS calculated the puncture depth and the table position automatically. LNS is recommended in CT-guided-interventions for dose and time reduction. Abstract: Purpose: The aim of this study was to analyse the radiation dose and quickness of needle interventions using a Laser Navigation System (LNS-group) compared with conventional method (control-group). Materials and methods: In this prospective, randomized, comparative study 58 patients (19 females, 39 males; mean age, 62.9 years) were punctured either with LNS ( n  = 29) or with conventional method with a skin mark of the puncture site ( n  = 29). In the LNS method the puncture site was marked with laser without additional CT. Thoracic and abdominal intervention was performed in 30 and 28 patients, respectively. Radiation dose and time of the procedures were analysed. Statistical significance was calculated according to the Mann–Whitney- U -test. Results: Mean target access path in the patients of the LNS group was 6.0 cm (range, 3.0–10.1 cm) and in the control group 6.0 cm (range, 1.0–10.3 cm). Time duration of complete intervention in the LNS group was 20:25 min (range, 07:00–34:00 min) and in the control group 28:00 min (range, 13:00–51:00 min). The dose-length-product (DLP) of intervention scan of the LNS group was 42.3 mGy cm (range, 10–125 mGy cm), and of the control group 59.7 mGy cm (range, 25–176.42 mGy cm). Conclusion: Using the LNS for CT-guided interventions results in faster intervention time with a lower dose.